Determinants of Customer Loyalty in the Zimbabwean Microfinance Sector - Mufaro Dzingirai; Noah Tshuma; Shingirai Sikomwe (IGI Global, 2023)
Recently, there has been an exponential increase in microfinance institutions leading to intense competition. This has impelled the interest of scholars, practitioners, and researchers in customer loyalty. Nonetheless, there is a dearth of empirical evidence on the determinants of customer loyalty in the microfinance sector. Accordingly, the main objective of this study is to establish the determinants of customer loyalty. Employing correlational research design with a sample size of 132 customers of microfinance institutions in Gweru who completed a highly structured questionnaire, the hypotheses are tested using Pearson correlation and regression analysis. The findings reveal that service quality, customer trust, and customer satisfaction have a strong statistically significant positive effect on customer loyalty. Nonetheless, a weak insignificant positive relationship between perceived microfinance image and customer loyalty is observed. It is, therefore, recommended that the managers should devise strategies to augment service quality, customer trust, and customer satisfaction.